Positional cloning without a genome map: using 'Targeted RFLP Subtraction' to isolate dense markers tightly linked to the regA locus of Volvox carteri. - Corrette-Bennett, J (1998)
The ability to isolate genes defined by mutant phenotypes has fueled the rapid progress in understanding basic biological mechanisms and the causes of inherited diseases. Positional cloning, a commonly used method for isolating genes corresponding to mutations, is most efficiently applied to the small number of model organisms for which high resolution genetic maps exist. We demonstrate a new and generally applicable positional cloning method that obviates the need for a genetic map. The technique is based on Restriction Fragment Length Polymorphism (RFLP) Subtraction, a method that isolates RFLP markers spanning an entire genome. The new method, Targeted RFLP Subtraction (TRS), isolates markers from a specific region by combining RFLP Subtraction with a phenotypic pooling strategy. We used TRS to directly isolate dense markers tightly linked to the regA gene of the eukaryotic green alga Volvox. As a generally applicable method for saturating a small targeted region with DNA markers, TRS should facilitate gene isolation from diverse organisms and accelerate the process of physically mapping specific regions in preparation for sequence analysis.